Cationic peptides in innate immunity - Bowdish, Dawn (Henry Stewart Talks, 2009)
Cationic peptides: a definition, The cathelicidins, The defensins, Antibiotic activity in vitro, Antibiotic activity: mechanisms of action, Antibiotic activity under physiologic conditions and in vivo, Bacterial evasion, Cationic peptides as immunomodulators, Are interactions with host cells receptor mediated or are there other mechanisms of action?, Role in human infectious disease, e.g. Mycobacterium tuberculosis infection, Role in human inflammatory disease, e.g. psoriasis, gla-3- Are cationic peptides pro- or anti-inflammatory?, Cationic peptides as drug targets